(untitled) (GUB Journal of Science and Engineering, 2020)
An online examination system is a software solution, which allows any industry or institute to arrange, conduct, and manage examinations via an online environment. Online Examination is an essential ingredient in electronic and interactive learning; both teachers and students are benefited from this. It’s very much useful during the current situation of the global pandemic Novel Corona Virus (COVID-19). In this paper, we proposed a system with automatic assessment technique is generated. The algorithms for calculations word frequency, matching keywords, analyzing linguistics, generating grades are proposed in this system. The system is implemented by using PhpStrom and MySQL. The performances of the system is evaluated with a large number of students and questions as well as answers, and we found the absolute (about 0.3%) and relative error (about 3.57%) which is quite satisfactory. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 54-59